N-Cinnamoylation of Antimalarial Classics: Effects of Using Acyl Groups Other than Cinnamoyl toward Dual-Stage Antimalarials - Ana Gomes (2015)
In a follow-up study to our reports of N-cinnamoylated chloroquine and quinacrine analogues as promising dual-stage antimalarial leads with high in vitro potency against both blood-stage Plasmodium falciparum and liver-stage Plasmodium berghei, we decided to investigate the effect of replacing the cinnamoyl moiety with other acyl groups. Thus, a series of N-acylated analogues were synthesized, and their activities against blood- and liver-stage Plasmodiumspp. were assessed along with their in vitro cytotoxicities. Although the new N-acylated analogues were found to be somewhat less active and more cytotoxic than their N-cinnamoylated counterparts, they equally displayed nanomolar activities in vitro against blood-stage drug-sensitive and drug-resistant P.falciparum, and significant in vitro liver-stage activity against P.berghei. Therefore, it is demonstrated that simple N-acylated surrogates of classical antimalarial drugs are promising dual-stage antimalarial leads.